2012
DOI: 10.1258/ebm.2012.011356
|View full text |Cite
|
Sign up to set email alerts
|

Role of chymase in diabetic nephropathy

Abstract: Chymase is an alternative pathway for angiotensin-converting enzyme in angiotensin II (Ang II) formation, and its expression is increased in human diabetic kidneys and in human mesangial cells (MCs) stimulated with high glucose. In addition, chymase activates transforming growth factor (TGF-β1) via an Ang II-independent pathway. The aim of this study was to evaluate the role of chymase on TGF-β1 activation in diabetic rats and in rat MCs (RMCs) stimulated with high glucose (HG). Diabetes was induced in male Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Mast cells are thought to be the main source of chymase; however, the present study failed to identify abundant mast cells in renal tissues by toluidine blue staining (data not shown). This result is consistent with the findings of a previous study, in which Cristovam et al ( 10 ) demonstrated that mast cells were absent in both control and diabetic kidneys, thus suggesting that chymase is synthesized by resident renal cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mast cells are thought to be the main source of chymase; however, the present study failed to identify abundant mast cells in renal tissues by toluidine blue staining (data not shown). This result is consistent with the findings of a previous study, in which Cristovam et al ( 10 ) demonstrated that mast cells were absent in both control and diabetic kidneys, thus suggesting that chymase is synthesized by resident renal cells.…”
Section: Discussionsupporting
confidence: 93%
“…The expression levels of the chymase encoding gene, RMCP-1, were markedly enhanced in diabetic kidneys. A previous study demonstrated that the mRNA expression levels of chymase were upregulated in glucose-stimulated mesangial cells ( 10 ). Mast cells are thought to be the main source of chymase; however, the present study failed to identify abundant mast cells in renal tissues by toluidine blue staining (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…56 On the other hand, examination of long-term-induced remodeling changes in an asthma model showed disease-aggravating roles by MC. 57 Similarly, data using chymase inhibitors have reported profibrotic actions for example via the generation of profibrotic Ang II or TGF-b1 in renal [58][59][60] or pulmonary fibrotic disease models, [61][62][63] but other studies show that downstream substrates of chymase like the matrix metalloproteinases activated either directly 19 or indirectly via the degradation of tissue inhibitor of metalloproteinases 18 are able to alleviate fibrosis. 64,65 These results indicate that similar to the general action of mast cells, mast cell chymase can have different roles, which depends on multiple factors including for example the involved type of organ, the type of injury, the kinetics of fibrosis development and so forth.…”
Section: Discussionmentioning
confidence: 98%
“…Specific synthetic chymase inhibitors attenuate Ang II production and alleviate renal fibrosis through inhibition of activation of TGF-β in animal models [ 26 ]. Chymostatin is a strong inhibitor of chymases and it can effectively inhibit Ang II production in the kidney [ 27 , 28 ] and ameliorate salt-dependent hypertension [ 29 ].…”
Section: Introductionmentioning
confidence: 99%